(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rapid growth of wearable devices has augmented the requirement for body centric wireless communication. In addition to this, to reduce the size of the device and its power consumption, it is also significant to develop a flexible antenna’s that may be incorporated for wearable applications. This paper presents the primary development of the wearable embroidery textile antenna for the wireless body area networks. The operating centre frequency ( fc ) of this wearable embroidery textile antenna is 2.40 GHz. Textile materials are used as the substrates as it has low relative permittivity and dielectric constant. A strip lines made up of conductive materials is used as radiating element. The nylon material used as a substrate material with a relative permittivity of 1.7 .The size of the antenna is very thin .The properties were analyzed for the proposed antenna.